Restorasi Mangrove Cegah Bencana Banjir Melalui Kegiatan Penanaman - Nurrachmania, Meylida; Rozalina, Rozalina; Triastuti, Triastuti; Damanik, Sarintan E; Simarmata, Marulam MT; Sidabukke, Simon H; Sihombing, Benteng H (Jurnal Pengabdian Masyarakat Sapangambei Manoktok Hitei, 2025)
Mangrove planting activities were carried out in the Kayu Besar village area, Bandar Khalipah District, Serdang Bedagai Regency, North Sumatra. The mangrove seedlings planted were of the Rhizopora mucronata species. The purpose of this activity was to minimize flooding in residential areas and improve the marine ecosystem, which is prone to flooding when the water rises and flows upstream and overflows into residential areas. Not only that, the planting of mangrove seedlings on the coast was carried out with the aim of minimizing abrasion in seawater, which could damage the coastal area. By raising awareness of the importance of mangrove trees, a higher level of conservation can be achieved. The function of mangroves here is as a barrier when seawater experiences high tides. With the presence of mangroves, the emergence of tidal waves can be dampened, thereby minimizing the impact of damage on land